Phosphate-Solubilizing Pseudomonas sp. Strain WS32 Rhizosphere Colonization-Induced Expression Changes in Wheat Roots - Ou, Kangmiao; He, Xiangyi; Cai, Ke; Zhao, Weirong; Jiang, Xiaoxun; Ai, Wenfeng; Ding, Yue; Cao, Yuanyuan (Frontiers in Microbiology, 2022)
Rhizosphere colonization is a prerequisite for the favorable application of plant growth-promoting rhizobacteria (PGPR). Exchange and mutual recognition of signaling molecules occur frequently between plants and microbes. Here, the luciferase luxAB gene was electrotransformed into the phosphate-solubilizing strain Pseudomonas sp. WS32, a type of plant growth-promoting rhizobacterium with specific affinity for wheat. A labeled WS32 strain (WS32-L) was applied to determine the temporal and spatial traits of colonization within the wheat rhizosphere using rhizoboxes experimentation under natural condition. The effects of colonization on wheat root development and seedling growth were evaluated, and RNA sequencing (RNA-seq) was performed to explore the transcriptional changes that occur in wheat roots under WS32 colonization. The results showed that WS32-L could survive in the wheat rhizosphere for long periods and could expand into new zones following wheat root extension. Significant increases in seedling fresh and dry weight, root fresh and dry weight, root surface area, number of root tips, and phosphorus accumulation in the wheat leaves occurred in response to WS32 rhizosphere colonization. RNA-seq analysis showed that a total of 1485 genes in wheat roots were differentially expressed between the inoculated conditions and the uninoculated conditions. Most of the transcriptional changes occurred for genes annotated to the following functional categories: “phosphorus and other nutrient transport”, “hormone metabolism and organic acid secretion”, “flavonoid signal recognition”, “membrane transport”, and “transcription factor regulation”. These results are therefore valuable to future studies focused on the molecular mechanisms underlying the growth-promoting activities of PGPR on their host plants.